Modern chromatographic analysis of vitamins - Leenheer, A. P. de; Lambert, Willy E., 1953-; Van Bocxlaer, Jan F., 1963- (Chromatographic science, 2000)
A collection and examination of the tremendous proliferation of information on chromatographic analysis of fat and water soluble vitamins. It extensively describes sample preparation and final measurement.